Component Separation with Porcine Acellular Dermal Reinforcement is Superior to Traditional Bridged Mesh Repairs in the Open Repair of Significant Midline Ventral Hernia Defects. Issue 8 (August 2014) - Richmond, Bryan; Ubert, Adam; Judhan, Rudy; King, Jonathan; Harrah, Tanner; Dyer, Benjamin; Thompson, Stephanie
The optimal technique for complex ventral hernia repair (VHR) remains controversial. Component separation (CS) reinforced with porcine acellular dermal matrix (PADM) has shown favorable results compared with series of conventional bridged VHR, but few comparative studies exist. We conducted a retrospective cohort study comparing 40 randomly selected patients who underwent CS/PADM reinforcement against an identical number of patients who underwent conventional open VHR with mesh at our institution. Patient characteristics, operative findings, outcomes, complications, reoperations, and recurrences were obtained by chart review. Fisher's exact/ t test compared outcomes between the two cohorts. Statistical significance was set as P < 0.05. Mean follow-up was 33.1 months. Patient groups did not differ significantly in race ( P = 1.00), age ( P = 0.82), body mass index ( P = 0.14), or comorbid conditions (smoking, chronic obstructive pulmonary disease, obesity, steroid use; P values 0.60, 0.29, 0.08, and 0.56, respectively). Defect size was greater in the CS/PADM group (mean, 372.5 vs 283.7 cm 2, P = 0.01) as was the percentage Ventral Hernia Working Group Grade III/IV hernias (65.0 vs 30.0%, P = 0.03). Recurrences were lower in the CS/PADM group (13.2 vs 37.5%, P = 0.02). Mesh infection was lower in the CS/PADM group (0 vs 23% in the bridged group, P = 0.002), all of which occurred with synthetic mesh. Indications for reoperation (recurrence or complications requiring reoperation) were also lower in the CS/PADM group (17.5 vs 52.5%, P = 0.002). Superior results are achieved with CS/PADM reinforcement over traditional bridged VHR. This is evidenced by lower recurrence rates and overall complications requiring reoperation, particularly mesh infection. This is despite the greater use of CS in larger defects and contaminated hernias (VHWG Grade III and IV). CS/PADM reinforcement should be strongly considered for the repair of significant midline ventral hernia defects.